Economic analysis of a solar assisted desalination system - Kalogirou, Soteris A. (My University, 1997)
This paper deals with an economic analysis of a solar assisted desalination system. The analysis is carried out for four types of applications, two domestic, a hotel and a village. It is shown that solar desalination is viable for the two bigger installations (hotel and village) with water prices below C£0.89/m3. It is also shown that the water cost is insensitive to the changes in method of payment or to small variations in direct costs. It is not worth operating the desalination system solely on solar energy due to the high cost of the desalination system and the diurnal nature of the solar input which implies high percentage of inactive time.
Keywords: Solar; Desalination system